Effect of Yoga and Physical Training on Health Related Physical Fitness Variables - Mukesh Kumar Taker, Dr. Pramjeet Singh Ghuman, Dr. Harbans Lal Godra (International Journal of Advanced Science and Technology, 2020)
It is a point of debate that there is a relationship between yoga and physical well-being. In order to evaluate the impact of yoga and physical training on health related physical fitness variables, a study was conducted on Ninety (90) untrained students from Poornima University, Jaipur during the academic year 2015 – 16 with age ranging from 18 to 21 years. This finding was used to conclude that yoga and physical training has are immensely impactful on health related physical fitness components of students.